Potential effect of the World Health Organization's 2011-2015 global leprosy strategy on the prevalence of grade 2 disability: a trend analysis - Catharina J Alberts; W Cairns S Smith; Abraham Meima; Lamei Wang; Jan Hendrik Richardus
OBJECTIVE: To assess different countries' chances of attaining the 2011-2015 global leprosy target set by the World Health Organization (WHO) and to assess the strategy's effect on the prevalence of grade 2 disability (G2D). METHODS: Trends in G2D rate were analysed for Brazil, China, India and Thailand and figures were compared with the WHO target: a 35% decrease by 2015 relative to the 2010 baseline. To estimate the prevalence of G2D in 2015 and 2035 for each country three assumptions were made: (i) maintenance of the current trend; (ii) attainment of the WHO target, and (iii) reduction of G2D by 50% every 5 years relative to 2010. FINDINGS: Since 1995, the G2D rate has decreased every 5 years in Brazil, China, India and Thailand by 12.7% (95% confidence interval, CI: 6.6-18.3), 7.7% (95% CI: 1.1-12.8), 53.7% (95% CI: 38.1-65.4) and 35.9% (95% CI: 23.4-46.3), respectively. New cases with G2D detected after 2010 will contribute 15% (Brazil), 3% (China), 2.5% (India) and 4% (Thailand) to the total prevalence of G2D in 2015. If no policies are changed, between 2015 and 2035, the prevalence of G2D will decrease by more than half in China, India and Thailand, and by 16% in Brazil. CONCLUSION: The implications of attaining the WHO target are different for each country and using indicators other than G2D prevalence will help monitor progress. The strategy will not immediately reduce the prevalence of G2D, but if it is applied consistently over the next 25 years, its long-term effect can be substantial.